Job Crafting: Work Engagement and Teacher Happiness - Meta Dwijayanthy; Missiliana Riasnugrahani; Cindy Maria (STAI Hubbulwathan Duri, 2023)
Happy teachers tend to perform better, be more capable of creating innovations, and produce new ideas in work so they help the organization reach its goals. This study aims to examine the role of job crafting towards happiness, mediated by work engagement in teachers as employees at their respective organizations. Participants of this study are 885 teachers who have worked in “X” Educational Foundation for at least one year. The instruments used are a job crafting scale that consists of 15 items, a calling scale with 12 items, a 9-item work engagement scale, and a happiness scale consisting of 8 items. All items in this instrument have been deemed valid and have reliability values of 0.763, 0.912, 0.934, and 0.758. The data obtained were analyzed using Model 4 of the SPSS Hayes Process. The findings of this study showed that there is a role of job crafting towards teachers’ happiness that is mediated by calling and work engagement. It was also found that job crafting has a significant direct effect on teachers’ happiness.